Evaluasi Penerapan K3 dan Risiko Kecelakaan pada Proyek Konstruksi di Kota Medan - Afriyani Siburian; Ival Ardyansyah Gultom; Muhammad Rafa Rizqi Lubis; Thya Ifhada Tambunan; Rizky Simanjuntak; Yuni Yolanda (JURNAL TECNOSCIENZA, 2026)
The construction sector is one of the industries with a relatively high risk of occupational accidents due to complex work activities, the use of heavy equipment, and dynamic working environments. These conditions make the implementation of Occupational Safety and Health (OSH) essential to protect workers from occupational accidents and health problems. This study was conducted to evaluate the implementation of OSH and identify potential work accident risks in construction projects in Medan City. A descriptive qualitative method was applied through field observations, documentation, and an OSH checklist. The results indicate that OSH implementation at the project site has generally been carried out well, as reflected by the availability of Personal Protective Equipment (PPE), safety signs, fire extinguishers, and evacuation routes. However, several unsafe conditions were still identified, including incomplete use of PPE, work at heights without adequate protection, and dusty working environments. These conditions may increase the risk of occupational accidents and health problems among workers. Therefore, improved supervision, worker awareness, and environmental control are needed to optimize OSH implementation and create a safer workplace.